On isomorphisms and invariants of finite dimensional complex filiform Leibniz algebras - Sattarovich, Rakhimov Isamiddin; Ural, Bekbaev (Taylor & Francis, 2010)
In this article, we propose an approach classifying a class of filiform Leibniz algebras. The approach is based on algebraic invariants. The method allows to classify all filiform Leibniz algebras (including filiform Lie algebras) in a given fixed dimensional case.